Endoscopic Optical Coherence Tomography (OCT): Advances in Gastrointestinal Imaging - Tejas S. Kirtane; Mihir S. Wagh (Gastroenterology Research and Practice)
In the rapidly evolving field of endoscopic gastrointestinal imaging, Optical Coherence Tomography (OCT) has found many diverse applications. We present the current status of OCT and its practical applications in imaging normal and abnormal mucosa in the esophagus, stomach, small and large intestines, and biliary and pancreatic ducts. We highlight technical aspects and principles of imaging, assess published data, and suggest future directions for OCT-guided evaluation and therapy.